Urban pattern recognition from multi-spectral satellite images and flood prediction using machine learning models - Tasnia, Rifah; Fuad, Sorder Md Farhan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.